ANALISIS LITERASI SAINS SISWA SMP AL HIDAYAH BANGKALAN PADA MATERI EKOLOGI DAN KEANEKARAGAMAN HAYATI INDONESIA - Syaifuddin, Ahmad; Tamam, Badrud; Qomaria, Nur; Yamins, Yamin; Putera, Dwi Bagus Rendy Astid (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2026)
This study aims to determine the level of scientific literacy of students at SMP Al Hidayah Bangkalan on the material of ecology and biodiversity of Indonesia. The type of research used is descriptive quantitative. The population of this study were students of SMP Al Hidayah. The sample used was class VII A and VII B with a total of 53 students using purposive sampling technique. Data collection technique through science literacy ability test. The results of this study can be concluded that the level of scientific literacy ability of students at SMP Al Hidayah Bangkalan is categorized as Sufficient, with an average value in the competency aspect of 44.25. As many as 62% of students get an average score in the sufficient category. The indicator explaining scientific phenomena is categorized as sufficient with an average score of 51.42. The indicator designing and evaluating investigations, the average score obtained is 41.98 with a sufficient category, while the average is 38.21 with a less category on the indicator interpreting evidence and data scientifically.